2023
DOI: 10.3390/antiox12051122
|View full text |Cite
|
Sign up to set email alerts
|

Pingwei San Ameliorates Spleen Deficiency-Induced Diarrhea through Intestinal Barrier Protection and Gut Microbiota Modulation

Abstract: Pingwei San (PWS) has been used for more than a thousand years as a traditional Chinese medicine prescription for treating spleen-deficiency diarrhea (SDD). Nevertheless, the exact mechanism by which it exerts its antidiarrheal effects remains unclear. The objective of this investigation was to explore the antidiarrheal efficacy of PWS and its mechanism of action in SDD induced by Rhubarb. To this end, UHPLC-MS/MS was used to identify the chemical composition of PWS, while the body weight, fecal moisture conte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 50 publications
1
3
0
Order By: Relevance
“…Nonetheless, to date, no reports have explored the connection between individuals with debilitating syndromes and the Eubacterium ruminantium group or the Eubacterium coprostanogenes group . In animal research, the Eubacterium ruminantium group has demonstrated the ability to fortify the intestinal barrier and reduce the body’s inflammatory response ( Fan et al, 2023 ; Hu et al, 2023 ), potentially mitigating frailty occurrence, aligning with our study’s findings. Regarding the Eubacterium coprostanogenes group , existing research links its increase to a higher risk of colorectal adenoma ( Zapico et al, 2022 ; Xiang et al, 2023 ), while its association with frailty warrants further investigation.…”
Section: Discussionsupporting
confidence: 88%
“…Nonetheless, to date, no reports have explored the connection between individuals with debilitating syndromes and the Eubacterium ruminantium group or the Eubacterium coprostanogenes group . In animal research, the Eubacterium ruminantium group has demonstrated the ability to fortify the intestinal barrier and reduce the body’s inflammatory response ( Fan et al, 2023 ; Hu et al, 2023 ), potentially mitigating frailty occurrence, aligning with our study’s findings. Regarding the Eubacterium coprostanogenes group , existing research links its increase to a higher risk of colorectal adenoma ( Zapico et al, 2022 ; Xiang et al, 2023 ), while its association with frailty warrants further investigation.…”
Section: Discussionsupporting
confidence: 88%
“…The Lachnospiraceae_XPB1014_group exhibited a specific negative correlation with Crohn’s disease, a form of inflammatory bowel disease [ 54 ]. The Eubacterium_ruminantium_group has been shown to alleviate colitis [ 55 ]. Solibacillus , part of the Bacillus genus, has an as-yet undetermined function.…”
Section: Discussionmentioning
confidence: 99%
“…In traditional Chinese medicine, the spleen-deficiency diarrhea is regarded as a prevalent gastrointestinal condition with diarrhea as the primary symptom ( Fan et al, 2023 ). The AQP3, AQP4, and AQP8 expression of colon was significantly decreased in rats with spleen-deficiency diarrhea, while their expression was significantly increased by administration with Pingwei San or Shenling Baizhu San ( Fan et al, 2023 ).…”
Section: Role and Regulation Of Aqp3 Expression In Diarrheamentioning
confidence: 99%
“…In traditional Chinese medicine, the spleen-deficiency diarrhea is regarded as a prevalent gastrointestinal condition with diarrhea as the primary symptom ( Fan et al, 2023 ). The AQP3, AQP4, and AQP8 expression of colon was significantly decreased in rats with spleen-deficiency diarrhea, while their expression was significantly increased by administration with Pingwei San or Shenling Baizhu San ( Fan et al, 2023 ). Similarly, treatment with a high dose of Atractylodis Rhizoma extract for consistent 10 days help prevent the spleen deficiency-induced diarrhea and reduce the pathological changes in colon tissue of mice, which might be associated with the enhanced expressions of both AQP3 and AQP8 in the colon ( Shi et al, 2019 ).…”
Section: Role and Regulation Of Aqp3 Expression In Diarrheamentioning
confidence: 99%